Preventing youth from falling into forbidden things by the narrations of Ahl al-Bayt (peace be upon them) (homosexuality as a model), a contemporary objective study. (Journal of the College of Basic Education, 2022)
This research deals with a problem that is considered one of the most important social problems, as it is not about the subject of (the transvestite), which has masculine characteristics and at the same time carries feminine characteristics that may prevail one of them over the other, but it talks about those who have sexual deviation, and have tendencies to imitate Westerners in practicing customs The bad ones, including (homosexuality), as a person lives in the midst of days a struggle with himself, so the soul wants to satisfy pleasures, then he has two options, either he is driven towards satisfying it, or pressured and suppressed in order to maintain integrity, and this is what is desired for his presence on the land of commission, as The mission of the Prophets and Messengers (peace be upon them) was to remind the person of his responsibility towards his religion, himself and others, and adhere to the nobility of morals, so leaving them means deviating from the right path. So the reason for going into this topic was to see some young people who have a tendency to imitate women significantly, which prompted me to search and follow up the problems that these people are facing, on YouTube I found the (Conan Baghdad) program looking for this issue and meeting with a perverted young man who tells his story that when He was an eight-year-old child who lived with his father, brother and sister, as for his mother, she was deceased and at the age of three years, his father was imprisoned due to disagreements between him and his relatives. A girl, and the child tells him that he is a boy and not a girl, and the neighbor’s son answers him. I know that, but I admire your beauty! Once the son of neighbors gave the child ten thousand dinars and took him to his home in an attempt to lure him to practice the heinous act with him, then the child went out of the house and went to buy what they needed from the markets and gave the money to the seller, but the shop owner refused to take the money because he knew of their condition, then he returned Home here his sister asked him, where did you get this? He told her that the market owner had given him these materials and did not tell her the rest of what had happened with him, so she warned him not to take anything from anyone again, and the neighbor’s son returned the ball with this child, so he got used to his position and made him feel that he was like a girl and not a boy until he grew up and grew up in such actions And from the bitter reality that the child lived, we realize the importance of following up and paying attention to the first building block in the proper upbringing of the child by the family, because family cohesion has an effective role in rebelling the deviations and abnormal tendencies from the norm among the individual, and accordingly, this research aims to be summarized as follows: 1- Explaining the reasons that lead to this forbidden act. 2- Clarifying the various kinds of punishment to discourage those who try to practice it. 3- Understanding the wisdom of God Almighty in prohibiting this act, and how to prevent it, and find solutions for treatment, if any. 4- Conclusion of the research, a brief summary. 5- Presenting the necessary recommendations for this.